Current circulation pattern in waters around Pulau Tinggi, Johor - Fredolin T. Tangang,; Mohd Syamil Mohd Yussof,; Liew, Juneng, (Universiti Kebangsaan Malaysia, 2007)
The current circulation pattern in waters around Pulau Tinggi, Johor was deduced based on the results of the Acoustic Doppler Current Profiler (ADCP) measurements during a period of 16 – 19 August 2004. It appears that the currents, regardless of tidal cycle, were predominantly southerly or southeasterly with average speeds of between 30 – 50 cm s-1. There appears to be current speed horizontal gradient toward the island as the current became weaker as it gets closer to the island. In the upper 10-15 m the currents were slowed by the prevailing winds which were predominantly southeasterly during the period. In the lower layer, about 10 m from seabed, the current speed reduced drastically due to bottom friction. The circulation pattern proves to be a typical pattern of a flow around an island where an evident of an eddy was captured in the observation data in a station located south of the island. Estimated shallow water Reynolds number indicates that the flow may produce a pair vortex of opposite direction and a central return flow at the southern end of the island.